2009
DOI: 10.1002/ijc.24249
|View full text |Cite
|
Sign up to set email alerts
|

Induction of myeloid‐derived suppressor cells by tumor exosomes

Abstract: Myeloid‐derived suppressor cells (MDSCs) promote tumor progression. The mechanisms of MDSC development during tumor growth remain unknown. Tumor exosomes (T‐exosomes) have been implicated to play a role in immune regulation, however the role of exosomes in the induction of MDSCs is unclear. Our previous work demonstrated that exosomes isolated from tumor cells are taken up by bone marrow myeloid cells. Here, we extend those findings showing that exosomes isolated from T‐exosomes switch the differentiation path… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
411
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 516 publications
(426 citation statements)
references
References 56 publications
13
411
0
2
Order By: Relevance
“…[25][26][27] Moreover, mice pretreated with TEXs also showed an accumulation of MDSCs in spleen, peripheral blood and lung. 28 Interestingly, heat shock protein 72 (HSP72) expressed at the surface of TEXs could induce activation of Stat3 and production of IL-6 in a TLR2/MyD88-dependent manner, thus promoting suppressive functions of MDSCs. 29 Furthermore, TEXs could be uptaken by immature DCs and then block DC maturation.…”
Section: Exosome-mediated Immunosuppression In Tumor-bearing Hostmentioning
confidence: 99%
“…[25][26][27] Moreover, mice pretreated with TEXs also showed an accumulation of MDSCs in spleen, peripheral blood and lung. 28 Interestingly, heat shock protein 72 (HSP72) expressed at the surface of TEXs could induce activation of Stat3 and production of IL-6 in a TLR2/MyD88-dependent manner, thus promoting suppressive functions of MDSCs. 29 Furthermore, TEXs could be uptaken by immature DCs and then block DC maturation.…”
Section: Exosome-mediated Immunosuppression In Tumor-bearing Hostmentioning
confidence: 99%
“…It was shown that melanoma and colorectal carcinoma-derived exosomes altered the monocyte differentiation into dendritic cells, leading to the generation of myeloid suppressive cells [94]. Furthermore, it was demonstrated that MDSC-mediated promotion of tumor progression was dependent on TGF- present on exosomes, but also depended upon the lipidic mediator prostaglandin E2 (PGE2) transported by tumor exosomes [95].…”
Section: Tumor Promoter Activitymentioning
confidence: 99%
“…Results on prostaglandins were obtained on exosomes released from a rat basophil leukemia cell line (RBL-2H3) [9], and it is required to screen more tumor-derived exosomes to assess whether the prostaglandin profile of exosomes could account for tumorprogression in-vivo. It is worth to note that incubating tumor exosomes with anti-PGE2 antibody decreases their effect on myeloid-derived suppressor cell expansion [95].…”
Section: E Pharmacology Of Exosomes: the Future Challengementioning
confidence: 99%
“…7,13 MDSCs are a heterogeneous population of bone marrow-derived myeloid progenitors and immature myeloid cells that expand dramatically during tumor growth, leading to an increased proportion of MDSCs in the peripheral blood and tumor microenvironments of cancer patients. 14,15 The MDSC phenotype varies by differentiation status and function in response to the environmental conditions of different cancers and generally has been termed as the HLA-DR ¡ CD33 C CD11b C cell population, including PMN-and MO-MDSCs, in many human cancers. [16][17][18][19] In humans, these tumor-associated MDSCs have drawn attention due to their role in tumor progression.…”
Section: Cox-2 Promotes Metastasis In Nasopharyngeal Carcinoma By Medmentioning
confidence: 99%